Predictors of financial dependency in old age in Peninsular Malaysia: an ethnicity comparison - Chan, Benjamin Yin Fah; Tengku Abdul Hamid, Tengku Aizan; Masud, Jariah; Paim, Laily (Canadian Center of Science and Education, 2010)
Aging is a global issue affecting countries including Malaysia. From an economic perspective, the government encourages senior citizens to be financially independent for as long as possible. To what extent the elderly is financially dependent is well documented but only few studies focus on an ethnic disparity perspective. This paper aims to identify the predictors of financial dependency among older Malaysians from the three ethnic groups. Data from an area study in Malaysia involving 806 older persons who participated in face-to-face interviews was used. Results showed that more than half of the respondents are financially independent while 44% depends on their children, sons or daughters in law, friends, neighbors or government financial assistance. Age and employment status were significant predictors of financial independence across all ethnic models. The study showed that there are different predictors of financial dependency by ethnic group and the result calls for different intervention strategies for the various ethnic elderly in achieving financial independence in old age.